PRESERVATION OF HOMBO BATU: BUILDING AWARENESS OF LOCAL WISDOM AMONG THE YOUNG GENERATION OF NIAS - Harefa, Darmawan (Universitas Nias Raya, 2024)
This service aims to enhance awareness of local wisdom among the young generation of Nias through the preservation of the Hombo Batu tradition. Utilizing an educational approach, various activities such as seminars, workshops, and hands-on practices were conducted to introduce the cultural values embedded in this tradition. The results indicate an increase in understanding and active participation of the youth in cultural preservation. Furthermore, collaboration with local communities and educational institutions strengthens the sustainability of this program. It is hoped that through these efforts, the youth of Nias can maintain and develop their cultural heritage while building a strong identity amidst the currents of globalization.